A Study of the Alfredian verse prefaces and epilogues - CLAUDIO CATALDI (Filologia Germanica)
This study takes into account the verse prefaces and epilogues associated with the translations of the Alfredian age, approaching them from a metrical standpoint. As I hope to demonstrate, both theMetrical Prefaceand theMetrical Epilogueto Alfred’s translation of Gregory’sPastoral Carefit the style of classical Old English poetry. Their author – be it Alfred or one of the scholars that convened at his court – was well-acquainted with the rules governing the traditional alliterative verse. The same applies to the briefMetrical Prefaceto the Old EnglishBoethius.On the other hand, theMetrical Prefaceto Wærferth’s translation of Gregory’s Dialogues displays features (such as lack of enjambement and anaphora) that are typical of late Old English poetry.These and other features suggest that this prefacemight bea late forgery,which was possibly inspired by similarAlfredianexamples. This interpretation would fit with the date of the only manuscript where Wærferth’s translation of Gregory’s Dialogues is accompanied by a preface (the eleventh century). The Metrical Epilogue to the translation of Bede’s Ecclesiastical History, which is also preserved in a single,eleventh-century copy, is characterised by the presence ofsimilar features.According to thisunderstanding,the Alfredian prologues and epiloguescan be read as examplesof the development of Old English poetry from early to late versification.